How Labour Governments Fall
IX, 186 p.
Keywords: What similarities exist between the reasons for Labour losing office in 2010 and those behind why previous Labour governments were defeated? This edited volume provides a detailed historical appraisal which considers the importance of themes such as economic performance; political leadership and the condition of the Conservatives in opposition.